Plasma miRNA expression profile in pediatric pineal pure germinomas - Fakhry, Mona; Elayadi, Moatasem; Elzayat, Mariam G.; Samir, Omar; Maher, Eslam; Taha, Hala; El-Beltagy, Mohamed; Refaat, Amal; Zamzam, Manal; Abdelbaki, Mohamed S.; Sayed, Ahmed A.; Kieran, Mark; et al. (Frontiers in Oncology, 2024)
Background Pure germinomas account for 40% of pineal tumors and are characterized by the lack of appreciable tumor markers, thus requiring a tumor biopsy for diagnosis. MicroRNAs (miRNA) have emerged as potential non-invasive biomarkers for germ cell tumors and may facilitate the non-invasive diagnosis of pure pineal germinomas. Material and methods A retrospective chart review was performed on all patients treated at the Children’s Cancer Hospital Egypt diagnosed with a pineal region tumor between June 2013 and March 2021 for whom a research blood sample was available. Plasma samples were profiled for miRNA expression, and DESeq2 was used to compare between pure germinoma and other tumor types. Differentially expressed miRNAs were identified. The area under the curve of the receive;r operating characteristic curve was constructed to evaluate diagnostic performance. Results Samples from 39 pediatric patients were available consisting of 12 pure germinomas and 27 pineal region tumors of other pathologies, including pineal origin tumors [n = 17; pineoblastoma (n = 13) and pineal parenchymal tumors of intermediate differentiation (n = 4)] and others [n = 10; low-grade glioma (n = 6) and atypical teratoid rhabdoid tumor (n = 4)]. Using an adjusted p-value <0.05, three miRNAs showed differential expression (miR-143-3p, miR-320c, miR-320d; adjusted p = 0.0058, p = 0.0478, and p = 0.0366, respectively) and good discriminatory power between the two groups (AUC 90.7%, p < 0.001) with a sensitivity of 25% and a specificity of 100%. Conclusion Our results suggest that a three-plasma miRNA signature has the potential to non-invasively identify pineal body pure germinomas which may allow selected patients to avoid the potential surgical complications.